Use of the Lorenz curve and the Gini index for the evaluation of HIV viral load distribution in an Italian community - Arsuffi, Stefania; Salvi, Martina; Calza, Stefano; Colombo, Fabio Riccardo; Alberti, Maria; Fioretti, Benedetta; Tiecco, Giorgio; Focà, Emanuele; Quiros-Roldan, Eugenia (Frontiers in Public Health, 2025)
BackgroundCommunity viral load (CVL) is defined as an aggregate measure of individual viral loads of people living with HIV who are receiving care in a specific community. It serves as a metric to evaluate the effectiveness of therapy programs. Our study aimed to analyze the overtime trend and the distribution characteristics of viral load.MethodsUsing the Lorenz curve, we investigated the demographic characteristics of individuals who comprised the top 10% of viral loads over the years. We applied the Gini index to measure the inequality in the distribution of viral load among the study population.ResultsOur data showed a progressive decrease in community viral load over the years, with a sharp decline after 2012 and a rebound in 2020. The Gini index had a specular trend during this period. In all the observed periods, the top 10% of viral loads showed a progressive increase in the proportion of female individuals and non-Italian nationals.ConclusionOur study highlighted the effectiveness and the improvement of the HIV care cascade over the years, with a decrease in community HIV viral load. The introduction of integrase inhibitors seemed to cause a rapid drop in community viral load in 2012 but with a notable discrepancy in the homogeneity of the population. It is also important to highlight the changes over time in the population representing the top 10% of viral loads, with a gradual but stable increase in the proportion of female and non-Italian individuals.